2019
DOI: 10.1029/2018jc014482
|View full text |Cite
|
Sign up to set email alerts
|

Retention and Leakage of Water by Mesoscale Eddies in the East Australian Current System

Abstract: Mesoscale eddies are ubiquitous in the ocean, transporting semi‐isolated water masses as well as advecting tracers and biota. The extent to which eddies impact the environment depends on the time they retain water parcels. Here we quantify retention times of mesoscale eddies in a (1/10)° model of the East Australian Current and its extension along the southeast coast of Australia. We find that retention times vary widely, between 3 and 357 days, but peak around 24 and 27 days for anticyclones and cyclones, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 83 publications
(150 reference statements)
4
26
0
3
Order By: Relevance
“…Comparing with SSH eddies, the mean RCLV radius (35.5 km) is approximately about half of the mean SSH eddy radius (72.4 km). Similar to this result, Cetina-Heredia et al (2019) showed that the solid body rotation radius is 0.6 and 0.5 the radius of anticyclonic and cyclonic eddies detected from velocity fields, respectively. In contrast with Abernathey and Haller (2018), no significant latitude dependence or relationship with deformation radius is visible in either RCLVs or SSH eddies.…”
Section: Radius Propagation Speed and Zonal Coherent Transportsupporting
confidence: 85%
“…Comparing with SSH eddies, the mean RCLV radius (35.5 km) is approximately about half of the mean SSH eddy radius (72.4 km). Similar to this result, Cetina-Heredia et al (2019) showed that the solid body rotation radius is 0.6 and 0.5 the radius of anticyclonic and cyclonic eddies detected from velocity fields, respectively. In contrast with Abernathey and Haller (2018), no significant latitude dependence or relationship with deformation radius is visible in either RCLVs or SSH eddies.…”
Section: Radius Propagation Speed and Zonal Coherent Transportsupporting
confidence: 85%
“…Comparing with SSH eddies, the mean RCLV radius (35.5 km) is approximately about half of the mean SSH eddy radius (72.4 km). Similar to this result, Cetina‐Heredia et al () showed that the solid body rotation radius is 0.6 and 0.5 the radius of anticyclonic and cyclonic eddies detected from velocity fields, respectively. In contrast with Abernathey and Haller (), no significant latitude dependence or relationship with deformation radius is visible in either RCLVs or SSH eddies.…”
Section: Census Of Lagrangian Vortices and Eulerian Eddiessupporting
confidence: 77%
“…However, Abernathey and Haller () concluded that RCLVs uniformly live shorter than SSH eddies and they only identified 1 RCLV with lifetime of 270 days in the eastern Pacific over more 20 years, against the number of 2,076 in the SSH eddy data set (Chelton et al ()). Also, Cetina‐Heredia et al () found eddies retain water for several months most commonly in the east Australian current system, some also retain water over a year but these are less frequent (their Figure ). In this study, therefore, we excluded the long‐lived eddies and focus on coherent eddies with lifetime shorter than 90 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations